2018
DOI: 10.1021/jacs.8b09992
|View full text |Cite
|
Sign up to set email alerts
|

π-Extended Corannulene-Based Nanographenes: Selective Formation of Negative Curvature

Abstract: A geometrically selective bottom-up synthesis of curved nanographenes is described. The synthetic methodology used involves the extension of the π-system of positively curved corannulene by a [4+2] cycloaddition reaction followed by cyclodehydrogenation (Scholl oxidation). By selecting the conditions for the Scholl oxidation, the formation of a sevenmembered ring that also confers negative curvature to the resulting nanographene can be activated, offering two topologically distinct, curved nanographenes from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 56 publications
3
122
0
Order By: Relevance
“…There are few examples on larger PAHs, where selective post‐functionalizing has been reported . In some cases a chlorination as side‐reaction occurs during the cyclization, when FeCl 3 is used as reactant, however, it seems that this is sometimes difficult to be controlled in terms of selectivity and yield …”
Section: Methodsmentioning
confidence: 99%
“…There are few examples on larger PAHs, where selective post‐functionalizing has been reported . In some cases a chlorination as side‐reaction occurs during the cyclization, when FeCl 3 is used as reactant, however, it seems that this is sometimes difficult to be controlled in terms of selectivity and yield …”
Section: Methodsmentioning
confidence: 99%
“…The single-crystal structure revealed the saddleshaped backbone with a highly distorted naphthalene moiety in the center. Recently, Martín et al [281] reported the synthesis of curved nanographene molecules from corannulene ( Figure 46). The Scholl reaction in the final step led to different products depending on the oxidation conditions.…”
Section: "Defects" Make the Differencementioning
confidence: 99%
“…These thirteend erivatives possess aryl substituents of varying degrees of electron-donating ability and with different substitution patterns.F urthermore, two unsymmetrical tetraarylfenestrindanes 10 and 12,e ach bearingt wo different kinds of aryl groups,w ere synthesized by using as tepwise Suzuki-Miyaura coupling strategy.T hus, the 1-(3,4-dimethoxyphenyl)-4,9,12tris(3,4-dimethylphenyl) (10)a nd the 1-(2,4-dimethoxyphenyl)-4,9,12-tris(2,3,4-trimethoxyphenyl) (12)d erivatives were obtained in 19 and2 0% yields, respectively,o ver two steps (Scheme 3). All new compounds were characterizedb y 1 Ha nd 13 CNMR spectroscopy and mass spectrometry.I na ddition, the structureo ft etrakis(4-tert-butylphenyl)fenestrindane, 6(4tBu), was characterizedb yX -ray crystallography (seet he Supporting Information). [24] Cyclization of symmetrical substrates Each of the thirteens ymmetrical tetraarylfenestrindanes was submitted to the Schollr eaction conditions (DDQ/TfOH) identical to those used for 6(34diOMe).…”
Section: Synthesis Of Symmetrical and Unsymmetrical Substratesmentioning
confidence: 99%
“…The hydroxy 1 Hr esonances were identified by H/D exchange with deuterium oxide. The methyl, methylene and methine 13 Cr esonances were distinguished by DEPT-90 and 135 experiments. Mass spectra were acquired by ESI or APCI with aT hermo QE xactive Focus Orbitrap, aB ruker SolariX 9.4 TF T-ICR, aB ruker Esquire 3000 Plus Ion Trap, or aS ynapt G2Si Q-IMS-TOFm ass spectrometer.S hown below are the experimental procedure and analytical data for all quadruply cyclized products without bridgehead functionalization.…”
Section: Experimental Section Generalmentioning
confidence: 99%